Direct comparison of the environmentally induced cracking resistance of 2nd and 3rd generation alloys, AA7050-T7651 and AA7085-T7651 - Ryan T. Euesden; Matthew E. Curd; Yichao Yao; Cameron Grant; N.J. Henry Holroyd; Philip B. Prangnell; Timothy L. Burnett (Materials & Design)
AA7050 and AA7010 aluminium alloys in overaged tempers have been a vital material for aerospace applications since their development in the 1970′s. Latest generation materials including AA7085, AA7449 and AA7037 have higher levels of Zn and reduced Fe and Si and offered some potential advantages but have suffered from Environmentally Induced Cracking (EIC) in service [1] and now in many cases are being replaced with previous generation materials [2]. Holroyd and Scamans [3] detailed some of the major risk factors associated with the new range of compositions and work by Schwarzenböck et al. [4] showed the stark EIC performance differences however the mechanistic understanding of these differences was still not clear. In this work, in-situ monitoring of 4 point bending tests conducted in conditions of 70 °C and 50 % RH was used to compare thick plate AA7050-T7651 and AA7085-T7651 as important alloys representative of the two generations of development. In both cases we find brittle intergranular cracks form, identified from the fracture surface, but in the case of AA7085 this is essentially the only mode of EIC whereas for AA7050 we see a mixed mode fracture surface which also includes intergranular modes of microvoid coalescence and transgranular cracking. It appears that cracking in AA7050 is only just viable. Short crack growth behaviour in the two materials allows us to identify an ‘intrinsic’ resistance of the grain boundaries to EIC and we find this is substantially greater in AA7050 compared to AA7085. This difference in performance is related to the ability of the grain boundary precipitate reactions to sustain hydrogen generation for continuous cracking. We find this process is very much disrupted in the case of AA7050 leading to a mixture of fracture modes and a commensurate reduction in crack growth rates by around an order of magnitude or more.